Evaluation of some new fungicide formulations to control sheath blight and brown spot in rice - N. SHARMA, J. S. LORE*, M. S. HUNJAN and (Indian Phytopathology, 2012)
Efficacy of some new fungicide formulations namely kresoxim methyl 40% + hexaconazole 8% (RIL-068/F1 48 WG), hexaconazole (RIL-01/F1 75 WG), propiconazole (Tilt 25 EC), hexaconazoleÂ (Contaf 5 EC), tricyclazole (Beam 75WP), and carbendazim 12% + mancozeb 63% (Saaf 75WP) was compared against economically important rice diseases namely sheath blight (Rhizoctonia solani), and brown spot (Drechslera oryzae), under laboratory and field conditions by artificial inoculation during kharif seasons 2009 and 2010. In addition, effects of the formulations on glume discoloration and grain quality parameters were evaluated. Kresoxim methyl 40% + hexaconazole 8% and hexaconazole (RIL-01/F1 75 WG) demonstrated highest efficacy followed by propiconazole against R. solani and D. oryzae pathogens under laboratory conditions. Carbendazim 12% + Mancozeb 63% were also effective against R. solani, but comparatively less effective against D. oryzae. Tricyclazole showed moderate effectivity against the test pathogens under laboratory. Kresoxim methyl 40% + hexaconazole 8% @ 0.1% was found to be the most effective fungicide against these diseases with lowest mean disease severity of 3.7%, 3.5% and 4.0%, respectively for sheath blight, brown and glume discoloration as compared to 44.9%, 31.1% and 12.6% in untreated checks of respective diseases. Spikelet sterility also was lower (5.6%) in the case kresoxim methyl 40% + hexaconazole 8% as compared to untreated check (19.8%). All the fungicide treatments gave significantly higher head rice recovery except carbendazim 12% + mancozeb 63% than the inoculated check. The total milling yield was not affected by the fungicides used in this study.